2022
DOI: 10.1038/s41598-022-22475-8
|View full text |Cite
|
Sign up to set email alerts
|

Dark plumes of glacial meltwater affect vertical distribution of zooplankton in the Arctic

Abstract: In polar regions, the release of glacial meltwater resulting in turbid plumes is expected to transform coastal waters with numerous consequences on the marine ecosystem. This study aimed to determine the influence of turbidity regimes on the vertical distribution of copepods together with their potential food (chlorophyll a fluorescence) and non-visual predators (gelatinous zooplankton). Hydrography, turbidity, suspended particulate matter and chlorophyll a were studied in July and August 2019 in West Spitsber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 77 publications
0
0
0
Order By: Relevance
“…Observational data and previous modelling studies showed that the continuing retreat of marine-terminating glaciers will negatively affect planktic and benthic communities, especially in enclosed shallow bays such as Brepollen (Fig. 7a) (Neder et al, 2022;Szeligowska et al, 2022Szeligowska et al, , 2021Torsvik et al, 2019). Indeed, we observed decreases in phytoplankton, zooplankton, and macrobenthos biomass, and delays in their peak occurrence close to the glacial fronts (by around 10-14 days as compared to the noSPM scenario, Fig.…”
Section: Ecosystem Dynamicssupporting
confidence: 62%
“…Observational data and previous modelling studies showed that the continuing retreat of marine-terminating glaciers will negatively affect planktic and benthic communities, especially in enclosed shallow bays such as Brepollen (Fig. 7a) (Neder et al, 2022;Szeligowska et al, 2022Szeligowska et al, , 2021Torsvik et al, 2019). Indeed, we observed decreases in phytoplankton, zooplankton, and macrobenthos biomass, and delays in their peak occurrence close to the glacial fronts (by around 10-14 days as compared to the noSPM scenario, Fig.…”
Section: Ecosystem Dynamicssupporting
confidence: 62%
“…Chlorophyll a algorithms that utilize satellite data tend to overestimate chlorophyll content, primarily due to the presence of colored dissolved organic matter (CDOM) in the water, mineral suspensions, and the influences of land and icebergs, which can affect the satellite signal. Recent studies indicate that in Svalbard fjords, there is an observed increase in the seasonal release of glacial runoff, accompanied by a positive trend in the darkening of seawater in this region (Konik et al., 2021 ; Szeligowska et al., 2022 ). The correlation between runoff and suspended sediment load is complex, with significant variability observed at the catchment level.…”
Section: Discussionmentioning
confidence: 99%